Penyelesaian Numerik Model Pemangsa-Mangsa dengan Metode Jaringan Fungsi Radial Basis Menggunakan Trigonometric Shape Parameter - Muhammad Thahiruddin; Mohammad Jamhuri (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
One mathematical model in the form of a system of nonlinear ordinary differential equations is the predator-prey model. The predator-prey model explains population changes of one prey population and one predator population due to changes in time. The radial basis function network method is used to find a numerical solution to the predator-prey model. The radial basis function network method can directly approximate the function and derivative of the prey-prey model using a basis function. The basis function used is a multiquadric basis function. Numerical solutions using the radial basis function network method obtained from this research show high accuracy and low error. The absolute error obtained from the two simulations with Δt = 0.01 each is 0.0066 in the first simulation and 0.022 in the second simulation. The errors obtained are relatively small because each only represents 0.66% of the initial value of the first type and 0.5% of the initial value of the second type. This shows that the radial basis function network method is efficient in calculating the predator-prey model solution.